Histological and Cytokine-Based Biomarkers in the Early Diagnosis of Cancer: Biomarker Berbasis Histologi dan Sitokin dalam Diagnosis Dini Kanker - Faisal, Ahmed Nassir; Abbas, Abbas Mohsin; M, Chayan; Mohsein, Osama A. (Indonesian Journal on Health Science and Medicine, 2025)
Background; Early detection of cancer significantly improves treatment outcomes and survival rates. Histological biomarkers, such as cellular atypia, mitotic figures, necrosis, and angiogenesis, play a crucial role in identifying malignancies. Cytokines like interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) are emerging as valuable biomarkers due to their involvement in cancer-related inflammation. Aims of the study; Evaluate the role of histological features and cytokine-based biomarkers, specifically interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), in the early diagnosis of cancer. Methodology; This case-control study, conducted from January to August 2024, included 150 cancer patients and 50 healthy controls. Inclusion criteria were adults aged 18-75 with a cancer diagnosis. Ethical approval was obtained. Tissue samples were processed for histology, and cytokine levels (IL-6, TNF-α) were measured using ELISA. Result; The results showed no significant differences in age and gender between patients and controls, but smoking, family history of cancer, and BMI were significantly higher in patients. Histological examinations revealed clear differences between cancerous and non-cancerous tissues. Cytokine levels were significantly elevated in patients, with strong correlations observed between cytokines and histological parameters. Finally, cytokines demonstrated high sensitivity and specificity, making them effective biomarkers for diagnosis. Conclusions; In conclusion, IL-6 and TNF-α are valuable biomarkers for cancer detection, demonstrating strong correlations with histological features. Their high sensitivity, specificity, and AUC support their potential in early diagnosis and prognosis of cancer. Highlights: Early Detection: IL-6 and TNF-α show high sensitivity and specificity, making them valuable for early cancer diagnosis. Histological Correlation: Strong associations between cytokine levels and tumor features like necrosis and angiogenesis support their diagnostic relevance. Clinical Utility: The study reinforces cytokines as potential non-invasive biomarkers, aiding in early screening and prognosis of cancer.